169 Hospital Mortality in 2, 437 Infants in the Australian, New Zealand and UK Boost II Trials of Neonatal Oxygen Saturation Targeting. (October 2012) - Tarnow-Mordi, WO; Stenson, B; Darlow, B; Brocklehurst, P; Morley, C; Davis, P; Juszczak, E; King, A; Simmer, K; Kirby, A; Donoghue, M; Ghadge, A; et al.
Abstract : Background: The optimal oxygen saturation (SpO2 ) for preterm infants is unknown. Three BOOST II trials in Australia, New Zealand and UK are comparing outcomes in infants < 28 weeks after randomisation to SpO2 targeting of 85–89% vs 91–95%, using masked oximeters. 1 In interim analysis the high target increased 36 week survival in infants whose oximeter had been upgraded with new, more accurate software. 2, 3 Methods: Pooled analysis of hospital mortality by target, overall and by old or new software. Results: There was no significant mortality difference between SpO2 targets overall. There was significant heterogeneity between old and new software on mortality (test for interaction p=0.006).* Using new software, targeting 91–95% increased hospital survival by 7.4% (from 76.8% to 84.2%) versus targeting 85–89% (p=0.0015).** Conclusions: Pending the primary outcome of disability free survival at 2 years it appears wise not to target 85–89%. References: Askie. BMC Pediatrics 2011; 11:6. Stenson. NEJM 2011; 364:1680–2. Johnston. Arch Dis Child Fetal Neonatal Ed. 2011; 96:429–33.